2022
DOI: 10.3390/molecules27248649
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits EMT in Bladder Cancer by Targeting Autophagy

Abstract: Melatonin, a naturally biosynthesized molecule secreted by the pineal gland, exhibits antitumor activities against several different types of cancer. The mechanisms of action of melatonin against tumor progression involve cellular apoptosis, antimetastatic activity, antioxidant and mutagenic effects, antiangiogenic activity, and the restoration of cancer immune surveillance. Melatonin has anticancer activity when administered alone or in combination with standard chemotherapeutic agents, with measurable improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Ehteda et al found that the combination of ALB with 2-methoxyestradiol synergizes the induction of apoptosis of colon cancer cells and improves the survival of HCT-116 tumor-bearing nude mice [ 47 ]. The synergy was based on the sum effect of microtubule-binding activity of both drugs, which differs from our approach, which is based on the possible sum of the different mechanisms of action attributed to ALB and MLT, as mentioned above [ 17 , 18 , 24 , 27 ]. On the other hand, MLT also has shown a chemosensitizing effect, since MLT downregulates the expression of ABC transporter ABCG2, inducing the synergistic cytotoxicity when combined with TMZ against GB cells and GB-stem cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehteda et al found that the combination of ALB with 2-methoxyestradiol synergizes the induction of apoptosis of colon cancer cells and improves the survival of HCT-116 tumor-bearing nude mice [ 47 ]. The synergy was based on the sum effect of microtubule-binding activity of both drugs, which differs from our approach, which is based on the possible sum of the different mechanisms of action attributed to ALB and MLT, as mentioned above [ 17 , 18 , 24 , 27 ]. On the other hand, MLT also has shown a chemosensitizing effect, since MLT downregulates the expression of ABC transporter ABCG2, inducing the synergistic cytotoxicity when combined with TMZ against GB cells and GB-stem cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…MLT is a highly lipophilic molecule that can diffuse through the cell membrane to interact with intracellular targets [ 22 ]. Several studies have shown the potential use of MLT in the treatment of cancer [ 23 ], including GB, with synergistic activity when combined with other drugs, attributed to the inhibition of multiple pro-survival pathways, the inhibition of efflux pumps, and the regulation of autophagy [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…MlT has a variety of physiological effects such as regulating the circadian rhythm, promoting sleep, enhancing immunity and scavenging free radicals, as well as anti-oxidation and anti-stress properties. MlT also displays antitumor activity including anti-proliferation, pro-apoptosis and anti-metastasis (10,11). Based on the fact that MlT effectively inhibits a variety of tumors, it has been used in combination with chemotherapy drugs to enhance the sensitivity of tumor cells to chemotherapy and inhibit tumor drug resistance.…”
Section: Introductionmentioning
confidence: 99%